Law Enforcement Against Morality Crimes through Restorative Justice by Gondomanan Police of Yogyakarta - Kurnia Dewi Anggraeny (Universitas Muhammadiyah Surakarta, 2022)
The goal of this study is to analyze the regulation of morality crimes and restorative justice in Indonesia, as well as the use of restorative justice by the Gondomanan Police of Yogyakarta to combat morality crimes.The statutory approach was applied in this study, which involved studying all laws and regulations in Indonesia relating to morality offences and restorative justice. The method of case approach is also used in this study, which examines cases involving morality offences. Restorative justice is the application of progressive legislation, in which the evolution of the purpose of punishment in Indonesia considers the interests of victim protection. The Gondomanan Police of Yogyakarta has been enforcing the law against morality crimes through restorative justice in accordance with Circular Letter of the Chief of Police No. 8 of 2018, which aims to bring together the perpetrators and victims, as well as several related parties, in the hopes of returning them to their original state. In this case, the police as investigators have given the victim enough chance to seek recompense from the criminal, and the culprit has consented to comply with the victim's request. The goal of this study is to learn more about how regulations for law enforcement against morality offences have evolved through restorative justice at the police level. The originality of this study stems from the fact that no cases of morals offences have ever been resolved by restorative justice.